EVOLUTION OF THERMAL PLUMES IN THE EARTH'S MANTLE - Ismail-Zadeh A.T.; Krupsky D.P.; Korotkii A.I.; Tsepelev I.A.; Schubert G. (My University, 2006)
Thermal plumes in the Earth’s mantle are formed at the core/mantle or upper/lower mantle boundary as a result of gravity instability in the thermal boundary layer (TBL), which can exist at these boundaries. At the same time, recent seismic tomography studies of the Earth’s mantle show clear evidence for low velocity anomalies (associated with individual mantle plumes) extending down to mid-mantle depths. The origin of mantle plumes at these depths is problematic because no TBL feeding the plumes has thus far been observed in the mid-mantle. In the present paper, we propose that plumes formed at the core/mantle boundary lose their tails (vertical conduits for hot material) during the thermal evolution of plumes.